Response of Different Growing Media on Germination and Seedling Growth of Albizia amara - Handa, A.K.; Dar, Shabir Ahmad; devi, Uma (Indian Journal of Agroforestry, 2020)
Selection of suitable growing media (potting mixture) plays an important role in raising the nursery of various tree species which helps in better establishment and growth when it transfer for planting in the field. The present investigation revealed that 1:1:2 ratio of sand, soil and FYM significantly influenced the seed germination of Albizia amara but the seedlings raised under 1:2:1 and 1:1:2 ratio of sand, soil and FYM recorded higher shoot length, root length and number of leaves. These ratios of sand, soil and FYM also gave higher biomass of individual seedlings.